Pentecostals, politics, and religious equality in Argentina - Aasmundsen, Hans Geir. (Religion in the Americas, 2016)
In Argentina, Pentecostalism had a breakthrough in the early 1980s, and today more than 10 per cent of the population are Pentecostals. The revival coincided with a socio-political transformation of Argentinean society. After half a century of dictatorships and Perónism, democracy was restored, and structural changes paved the way for an autonomisation of the political, economic, scientific and religious spheres. The "new" form of society that developed resembles what in this study is called a Western model, which to a large degree has been, and still is, spread on a global scale. In this book, Aasmundsen examines the religious sphere and how Pentecostals relate to society at large, and the political and judicial spheres in particular.